2020
DOI: 10.1038/s41598-020-65989-9
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Burden in Children, Adults and Older Adults in Slovenia: A Nationwide Database Study

Abstract: Anticholinergic burden has been widely studied in specific patient populations with specific conditions. However, the prevalence in the general population is poorly understood. This retrospective cross-sectional study was a nationwide database analysis of outpatient prescriptions of anticholinergic medications. The study was based on Slovenian health claims data of all outpatient prescriptions in 2018. Anticholinergic burden was evaluated using the Anticholinergic Cognitive Burden scale. Three age groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…These data suggest that already in younger patients, AB might be associated with adverse effects. So far, only a single study has provided a comprehensive overview of the prevalence of AB in all age groups of a population [ 18 ]. However, in this study, age categories were defined broadly and AB prevalences were not stratified by sex within age groups.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that already in younger patients, AB might be associated with adverse effects. So far, only a single study has provided a comprehensive overview of the prevalence of AB in all age groups of a population [ 18 ]. However, in this study, age categories were defined broadly and AB prevalences were not stratified by sex within age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Anticholinergic medications are commonly prescribed 1 3 yet a growing body of evidence has demonstrated that their use is associated with a higher risk of incident cognitive impairment 4 6 . This literature has been reviewed multiple times in older adults, whereby anticholinergic medications have been consistently associated with cognitive decline and dementia 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…There are few population-based studies that have assessed the extent to which children are exposed to anticholinergic medicines 1 . Most studies examining anticholinergic medicines in children have focussed on the use of medicine classes for specific indications, for example, asthma or overactive bladder, rather than providing population-based estimates for the use of anticholinergic medicines like the studies in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticholinergics are commonly used to treat not only urinary incontinence due to overactive bladder (OAB) but also chronic obstructive pulmonary disease (COPD), asthma, Parkinson’s disease, dizziness and motion sickness. Many studies show the ill effects of anticholinergics on cognition resulting in increased morbidity and mortality [ 1 , 2 ]. However, the interaction of anticholinergic medications and cumulative anti-cholinergic burden (ACB) of different medications are not well known in general population and amongst health care professionals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%